A case study of eating disorder: Bulimia Nervosa and its Islamic perspective - Selian, Sri Nurhayati; Abd Hamid, Siti Rafiah (2013)
Bulimia Nervosa (BN) is primarily a psychiatric disorder characterized by severe disturbances of eating behavior. Bulimia nervosa is one of the most common eating disorder and is characterized by compulsive eating extremely followed by compensatory efforts to purge calories and avoid weight gain. In fact, eating disorder has become a gowning issues in adolescence. Hey are very concerned about their physical appearance but are unable to control their over eating habits. From the Islamic perspective, health is viewed as one of the greatest blessings that Allah has bestowed on mankind. Various Qur’anic verses and texts within Islam promote the healthy eating habits ie. Balanced diet and eating in moderation. The Prophet Muhammad (pbuh) has strictly forbidden overeating in the following hadith: “overeating is the source of all diseases,” (narrated by Al-Sayuthy cited in Abdillah, 1996). This study identifies factors which lead to eating disorder and results in obesity. Hence, obesity has been identified as a risk factor for the development of bulimia nervosa among those who try to lose weight.